TIMELY IMPLEMENTATION OF PERSONAL EDUCATION MEASURES IN THE CONTEXT OF GLOBALIZATION - Khalilova Barnogul Abdulazizovna; Qodirova Dilshoda Abdunabiyеvna; Tuychiyeva Hilola Zokirjon qizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article describes the importance of educating a harmoniously developed personality in society, explaining to the new generation important tasks such as strengthening independence, valuing and protecting a peaceful and peaceful life, being vigilant. It describes measures to protect young people from various ideological threats, outlines the problems of increasing the level of coverage of the population with higher education, regular and systematic work on training, education and spiritual propaganda using advanced methods.